Dead Stop : Sydney Rose Parnell #2 - Nickless, Barbara (Seattle : Thomas & Mercer, 2017)
"The search for a missing child leads a courageous railway cop down a twisted trail of murder. It's been five months since Special Agent Sydney Parnell survived a violent confrontation with a gang of brutal thugs, an encounter that left her physically and emotionally scarred. Deep down, Sydney fears she isn't ready for another investigation. But when a woman is murdered on the train tracks and a child goes missing, she knows she's the only one who can lead the hunt for the killer. While Denver police and the FBI chase down blind alleys, Sydney focuses on a single cryptic clue left behind at the crime scene--one that will send her down a path of greed, violence, and long-ago love. With Denver beset by a series of monsoonlike thunderstorms that threaten to flood the city, Sydney and her K9 partner, Clyde, must wade through a murky trail of murder that stretches back thirty years--all to rescue a child ... and catch a killer with a long memory and an insatiable appetite for destruction."--Provided by publisher.
Keywords: Murder -- Investigation -- Fiction; Missing children -- Fiction; Railroad police -- Colorado -- Denver -- Fiction; Police dogs -- Fiction; FICTION -- Mystery & Detective -- Police Procedural; FICTION -- Mystery & Detective -- Women Sleuths; Missing children; Murder -- Investigation; Police dogs; Railroad police; Colorado -- Denver; Books on CD. -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Fiction; Suspense fiction; Thriller fiction; Detective fiction; Mystery fiction